Pengaruh Pemberian Alga Coklat (Sargassum sp.) Terhadap Enzim Katalase Kelenjar Submandibularis Tikus Rattus Norvegicus Strain Wistar Akibat Iradiasi Linear Energy Transfer (LET) Rendah - sariano ferni (Universitas Muhammadiyah Surabaya, 2017)
Background: Background: Intraoral radiography use some lower LET (Linear Energy Transfer) and could penetrate submandibular salivary gland. Radiography have negative impact which is decrease catalase enzyme of human body. Brown algae (Sargassum sp.) has a flavonoid antioxidant, polysaccharides as Fucoidan and alginat (Na-alginat) can be used for immunomodulator, antioxidative and activation modulation of immune. Purpose: To knowing effectiveness of brown algae (Sargassum sp.) on activity catalase enzyme submandibular salivary gland Rattus Novergicus strain Wistar with irradiation low LET. Material and Methods: 28 samples of Rattus Novergicus strain Wistar, weight 200gr, age 2-3months, gender male, sample divide into 4 groups, K1 (control with brown algae dosage 0,018mg/kgbw) K2 (use brown algae and irradiation 4 times), K3 (use brown algae and irradiation 8 times), K4 (use brown algae and irradiation 14 times). Brown algae been given 7days before apply irradiotion on day 8, then did euthanasia and took submandibular salivary gland. After that did measurement activity of catalase enzyme and counted by spectrophotometer with 240 λ. Result: Data were analyze by Shapiro-wilk, One Way ANOVA and Bonferroni. The activity of catalase enzyme have increased; 0,2586 ± 0,1050 (K1), 0,2595 ± 0,0630 (K2), 0,3252 ± 0,1663 (K3), 0,3668 ± 0,0852 (K4) but theres no significant differences activity of catalase enzyme between one group to other group. Conclusion: Brown algae dosage 0,018mg/kgbw can’t increase activity of catalase enzyme on Rattus Novergicus strain Wistar.